Forty years of warming: Environmental change in marine coastal habitats on Svalbard between 1981 and 2022 - Węsławski, Jan Marcin; Urbański, Jacek A. (Polish Polar Research, 2024)
Temperature rise, together with resultant ice cover retreat in Svalbard, changes in hydrology and geomorphology of fjords and coastal waters, is presented as forming force for the marine habitats. Satellite data show increase of habitat complexity following the tidal glaciers retreat and emergence of new (315 km) and complex shoreline. Most evident changes occur in the inner-fjord settings of the west coast of the archipelago, while habitats of exposed marine shores and eastern sector of Svalbard remain little changed. It is hypothesized, that decrease in ice cover opens more space for life compared to the cold period.